Catalyst for preparing pyromellitic dianhydride through durene gas-phase oxidation, preparation method of catalyst and method for producing pyromellitic dianhydride

By using high-length-diameter zinc oxide nanorods as an inert support and spraying active components, the problems of poor mechanical stability of the catalyst and low homoanhydride yield are solved, and higher catalyst life and reaction selectivity are achieved.

CN119869571AActive Publication Date: 2025-04-25CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202311396058.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-25
Publication Date
2025-04-25
Estimated Expiration
2043-10-25

AI Technical Summary

Technical Problem

In the gas-phase oxidation method of existing catalysts, there are problems such as poor mechanical stability, short catalyst life and low homoanhydride yield.

Method used

A one-dimensional structure zinc oxide nanorod with a high aspect ratio is used as a catalyst for an inert support, and the active components are uniformly coated by spraying, and a gas-phase oxidation reaction is carried out in a fixed bed reactor.

Benefits of technology

The mechanical stability of the catalyst and the yield of homoanhydride are significantly improved, the life of the catalyst is extended, and the selectivity of the reaction is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119869571A_ABST
    Figure CN119869571A_ABST
Patent Text Reader

Abstract

The invention provides a catalyst for preparing pyromellitic dianhydride through durene gas-phase oxidation, a preparation method of the catalyst and a method for producing pyromellitic dianhydride. The catalyst comprises an inert carrier and an active component, the inert carrier is a zinc oxide nanorod. The catalyst provided by the invention effectively improves the binding force between the active component coating of the catalyst and the inert carrier, effectively reduces the abrasion of the catalyst and the loss of the active component caused by the shedding of the coating, and is beneficial to the improvement of the selectivity and mechanical stability of the catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of catalysis, and in particular to a catalyst for producing homoanhydride by gas-phase oxidation of durene, a preparation method thereof, and a method for producing homoanhydride. Background Art

[0002] With the development of the petroleum refining industry, large-scale ethylene plants, catalytic reforming plants and aromatics plants will produce a large amount of C10 aromatics as by-products. How to efficiently and economically utilize C10 aromatic resources has become one of the important research directions of petrochemical industry. Duroylene in C10 aromatics can be used to produce pyromellitic dianhydride (PMDA, homoanhydride). Homoylene is a fine chemical intermediate with high added value, with excellent heat resistance, chemical resistance and dielectric properties. It can be used to produce monomers of heat-resistant resins such as polyimide and polyimidazole, pharmaceutical intermediates, cross-linking agents for high-end resin materials, etc. Its related products are widely used in high-precision industries such as aerospace, 5G communications, and flexible displays. Therefore, separating duroylene from C10 aromatics and preparing homoanhydride is an effective way to utilize C10 aromatic resources, which has important research significance and significant economic value. Summary of the invention

[0003] The technical problem to be solved by the present invention is to provide a catalyst using zinc oxide nanowires with a one-dimensional structure as an inert carrier of a homogenized anhydride catalyst.

[0004] At present, the preparation of homoanhydride using durene as raw material mainly adopts gas phase oxidation method, which relies on fixed bed reactor. The advantage of this method is that homoanhydride is directly generated in one step, the atomic utilization efficiency is high, and the production process is green and environmentally friendly. The disadvantages of this method are that there are many side reactions, the yield of homoanhydride is low, and the catalyst life is short. The main active components of the catalyst used in the gas phase oxidation method are vanadium oxide and titanium oxide, and the active components are configured into slurry and sprayed onto an inert carrier.

[0005] Existing studies have shown that the choice of different inert carriers will affect the reaction performance. In an early study (Journal of Shenyang Institute of Technology, 1998, 03, 35-39), researchers compared the use of α-Al 2 O 3 The activity of catalysts made of four inert carriers, namely, silicon carbide, ceramic balls, α-SiC and β-SiC, at a certain reaction temperature. The results show that the crystal structure of α-SiC is more suitable for the requirements of this reaction for inert carriers. However, due to the high price of silicon carbide, the current industrial carrier selection is mainly based on ceramic balls. One of the shortcomings of existing catalysts is that the mechanical stability of the catalyst is poor, and the coating is prone to fall off, which affects the life of the catalyst. Therefore, it is urgent to find an inert carrier with excellent supporting performance and prepare a catalyst with high coating strength.

[0006] Zinc oxide nanomaterials have become one of the materials of concern in the field of nanotechnology due to their great potential for success in the fields of chemistry, electricity, and optics. The special surface effect of nanomaterials enables them to exhibit excellent properties far exceeding those of traditional materials in the field of catalysis, but the developed surface effect causes nanoparticles to agglomerate more easily. How to effectively disperse nanoparticles is an issue that cannot be ignored in the design of nanomaterials. The present invention is the first to study and discover that one-dimensional zinc oxide nanowires with a high aspect ratio as an inert carrier catalyst exhibit excellent performance in the synthesis of homoanhydrides. Compared with catalysts with alumina, silicon carbide, and porcelain balls as inert carriers, the catalyst of the present invention has the characteristics of high mechanical stability and high yield.

[0007] It is speculated that the one-dimensional zinc oxide nanorods have a high aspect ratio, a small size effect of nanoparticles retained radially (diameter nanometer level), and the ability to introduce macroscopic characteristics of bulk materials in the longitudinal direction (length micrometer level), which can effectively reduce the surface energy of nanomaterials, avoid aggregation and sintering during use, and have excellent mechanical stability. At the same time, the zinc oxide nanorods have a unique one-dimensional structure of small scale, so that the active component coating and the carrier have good bonding properties, enhance the bonding force between the coating and the carrier, and are conducive to improving the mechanical stability of the catalyst. At the same time, its low surface energy can avoid the agglomeration of active components, which is conducive to the uniform distribution of active components on it.

[0008] To achieve the aforementioned objectives, according to a first aspect of the present invention, a catalyst for preparing homoanhydride by gas phase oxidation of durene is provided, the catalyst comprising an inert carrier and an active component; the inert carrier is zinc oxide nanorods.

[0009] According to a second aspect of the present invention, the present invention provides a method for preparing the catalyst, the method comprising:

[0010] (a) obtaining zinc oxide nanorods for serving as an inert support;

[0011] (b) obtaining a precursor slurry containing catalyst active components;

[0012] (c) spraying the precursor slurry onto the zinc oxide nanorods by a spraying method, and calcining to obtain the catalyst.

[0013] According to a third aspect of the present invention, the present invention provides a method for producing a homohydric anhydride, wherein a fixed bed reactor is used, and in the presence of the catalyst of the present invention, the raw material durene is contacted with an oxygen-containing gas, wherein the contact conditions include: the mass concentration of durene is 10-40 g / cm 3 , gas hourly volume space velocity is 4000-8000hr -1 , the reaction temperature is 350-500°C, and the reaction pressure is normal pressure.

[0014] Compared with the prior art, the catalyst of the present invention uses one-dimensional zinc oxide nanorods with a high aspect ratio as an inert carrier, which can produce a bonding effect on the coating, exert an excellent carrier effect, and effectively improve the mechanical stability and yield of the catalyst.

[0015] When the catalyst of the present invention is used for producing homoanhydride by gas phase oxidation of durene, good technical effect is achieved.

[0016] The catalyst of the present invention effectively improves the bonding force between the catalyst active component coating and the inert carrier, effectively reduces the catalyst wear and active component loss caused by coating shedding, and is beneficial to improving the selectivity and mechanical stability of the catalyst. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 is a SEM image of the zinc oxide nanowires synthesized in Preparation Example 1.

[0018] Figure 2 This is the XRD pattern of the zinc oxide nanorods synthesized in Preparation Example 1. DETAILED DESCRIPTION

[0019] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0020] The present invention provides a catalyst for preparing homoanhydride by gas phase oxidation of durene, the catalyst comprising an inert carrier and an active component; the inert carrier is a zinc oxide nanorod. The catalyst using the one-dimensional zinc oxide nanowire with a high aspect ratio as an inert carrier exhibits excellent performance in synthesizing homoanhydride, and compared with catalysts using aluminum oxide, silicon carbide, ceramic balls and the like as inert carriers, the catalyst of the present invention has the characteristics of high mechanical stability and high yield.

[0021] According to a preferred embodiment of the present invention, the aspect ratio of the zinc oxide nanorods is 40-130, for example, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 100, 105, 110, 115, 120, 125, 130, preferably 42-55. This can further improve the mechanical stability and yield of the catalyst.

[0022] According to a preferred embodiment of the present invention, the length of the zinc oxide nanorods is 3.0-3.9 μm, such as 3.5-3.9 μm, 3.2-3.7 μm, or 3.0-3.5 μm, thereby further improving the mechanical stability and yield of the catalyst.

[0023] According to a preferred embodiment of the present invention, the diameter of the zinc oxide nanorods is 30-70 nm, for example, 30-50 nm, 40-60 nm, or 40-70 nm, thereby further improving the mechanical stability and yield of the catalyst.

[0024] According to a preferred embodiment of the present invention, the crystal phase of the zinc oxide nanorods is hexagonal zincite, thereby further improving the mechanical stability and yield of the catalyst.

[0025] In the present invention, the content range of the inert carrier and the active component can be selected from a wide range, which is exemplary but not limiting the scope of the present invention. Based on the total weight of the catalyst, the content of the carrier is 60-97wt%;

[0026] In the present invention, the active component is based on the total weight of the catalyst, and the active component is calculated based on the weight of its corresponding oxide. The content of the active component is 1-50wt%, preferably, the content of the active component is 3-40wt%, and 10wt% is used as an example to illustrate the advantages of the present invention.

[0027] In the present invention, there is no special requirement for the active components. The following exemplary description is not intended to limit the scope of the present invention. According to one embodiment of the present invention, the active components of the catalyst include a main active component oxide and an auxiliary active component element oxide, and the main active component oxide includes vanadium oxide and titanium oxide.

[0028] According to a preferred embodiment of the present invention, the auxiliary active component element is selected from at least one of sub-group metal elements and non-metal elements.

[0029] According to a preferred embodiment of the present invention, preferably, the mass ratio of the vanadium oxide, titanium oxide, and co-active component element oxide is (0.005-0.5):1:(0.003-0.28), thereby further improving the catalyst yield.

[0030] According to a preferred embodiment of the present invention, preferably, the subgroup metal element includes one or more of zirconium, niobium and tungsten; thereby, the target product yield of the catalyst can be further improved.

[0031] According to a preferred embodiment of the present invention, the non-metallic element includes one or more of phosphorus and boron; thereby, the yield of the target product of the catalyst can be further improved.

[0032] In the present invention, the mass ratio of the vanadium oxide, titanium oxide, subgroup metal element oxide and non-metal element oxide can be selected in a wide range, for example, the mass ratio of the vanadium oxide, titanium oxide, subgroup metal element oxide and non-metal element oxide is (0.005-0.5):1:(0.0001-0.2):(0.001-0.08). This can further improve the target yield of the catalyst.

[0033] According to a preferred embodiment of the present invention, preferably, the mass ratio of vanadium oxide, titanium oxide, subgroup metal element oxide and non-metal element oxide is (0.05-0.45):1:(0.0005-0.002):(0.002-0.05), thereby further improving the target yield of the catalyst.

[0034] According to a preferred embodiment of the present invention, the auxiliary active component preferably includes niobium oxide, tungsten oxide and phosphorus oxide; preferably, the mass ratio of the three is 0.01-1: 0.01-1: 1. This can further improve the target yield of the catalyst.

[0035] The present invention has no special requirements for the preparation method of the inert carrier. Any inert carrier that meets the above characteristics can achieve the purpose of the present invention. According to the present invention, the preparation method of the inert carrier preferably includes the following steps: (1) obtaining a mixed solution including a zinc source, polyethylene glycol, water, ethanol and sodium hydroxide;

[0036] (2) transferring the mixed solution to a hydrothermal reactor for hydrothermal reaction;

[0037] (3) washing, filtering, drying, calcining and optionally forming the reaction product after the hydrothermal reaction is completed;

[0038] Wherein, in step (1), the mass ratio of water to ethanol is 0-2:1 (0 means infinitely close to 0 but not 0), preferably 0.005-0.5:1, preferably 0.01-0.4, for example 0.05, 0.25, 0.4. It is inferred that the above technical solution can achieve the regulation of the dielectric constant of the solution, and the inert carrier of the present invention can be prepared.

[0039] The present invention has no special requirements for the hydrothermal reactor, for example, it can be a stainless steel hydrothermal reactor with a polyethylene tetrafluoro lining.

[0040] In the present invention, there is no special requirement for obtaining a mixed solution including a zinc source, polyethylene glycol, ethanol and sodium hydroxide. For example, it can generally be carried out according to the following steps: weigh the zinc source and polyethylene glycol, dissolve them in deionized water, stir until completely dissolved, then add ethanol to obtain a mixed solution and stir, and when white foam is observed in the solution, add NaOH and continue stirring until completely dissolved.

[0041] In the present invention, the dosage of each substance can be selected in a wide range, and the commonly used ranges in the art can be applied to the present invention. The following is an exemplary description, but the scope of the present invention is not limited thereto.

[0042] In the present invention, the weight ratio of the zinc source to the ethanol can be selected in a wide range, for example, the weight ratio is 0.001-0.1, and 0.015 is used as an example to illustrate the advantages of the present invention, but the scope of the present invention is not limited thereto.

[0043] In the present invention, the weight ratio of polyethylene glycol to ethanol can be selected in a wide range, for example, the weight ratio is 0.001-0.1, and 0.02 is used as an example to illustrate the advantages of the present invention, but the scope of the present invention is not limited thereto.

[0044] In the present invention, the weight ratio of water to ethanol can be selected in a wide range, for example, the weight ratio is 0-2:1 (0 means infinitely close to 0, not 0), preferably 0.005-0.5:1, preferably 0.01-0.4, for example 0.05, 0.25, 0.4. However, the scope of the present invention is not limited thereto.

[0045] In the present invention, the weight ratio of sodium hydroxide to ethanol can be selected in a wide range, for example, the weight ratio is 0.01-0.1, and 0.03 is used as an example to illustrate the advantages of the present invention, but the scope of the present invention is not limited thereto.

[0046] According to a preferred embodiment of the present invention, preferably, the weight ratio of the zinc source, polyethylene glycol, water, ethanol and sodium hydroxide is 0.001-0.1: 0.001-0.1: 0.005-0.5: 1: 0.01-0.1.

[0047] According to a preferred embodiment of the present invention, preferably, in step (1), the polyethylene glycol is one or more of polyethylene glycol 2000, polyethylene glycol 10000 and polyethylene glycol 20000, preferably polyethylene glycol 20000. The use of the polyethylene glycol with the above preferred molecular weight can achieve the reaction with Zn in the solution. 2+ A strong interaction is generated, which is beneficial to the directional growth of ZnO crystals.

[0048] In the present invention, there is no special requirement for the zinc source. It is illustrative but not limiting to the scope of the present invention. Preferably, in step (1), the zinc source is one or more of zinc acetate, zinc sulfate and zinc nitrate, preferably zinc acetate.

[0049] In the present invention, the optional range of hydrothermal reaction conditions is relatively wide. For the present invention, in the preferred step (2), the hydrothermal reaction conditions include: a reaction temperature of 80-200°C, preferably 100-150°C, for example, 100°C, 120°C, 140°C, 150°C, etc.

[0050] In the present invention, the optional range of hydrothermal reaction conditions is relatively wide, and the time of the hydrothermal reaction can be determined as needed. For example, the general reaction time is 8-24 hours, preferably 10-18 hours, for example, 10 hours, 12 hours, 14 hours, 16 hours, and 18 hours.

[0051] The present invention has no special requirements for washing, and there is no special requirement for the type of detergent. For the present invention, in step (3), the detergent is preferably one or more of water, methanol and ethanol. Preferably, the detergent is water and / or ethanol. Usually, water and ethanol are used for washing multiple times, generally more than 3 times.

[0052] In the present invention, there are no special requirements for the drying, calcining and molding methods. The following is an exemplary description, but the scope of the present invention is not limited thereby.

[0053] For example, the drying temperature is 40-100° C., preferably 60-80° C.; the drying time is, for example, 4-8 hours.

[0054] For example, the calcination temperature is 300-600° C., preferably 400-500° C., and the calcination time is, for example, 3-6 hours.

[0055] For example, the forming method is extrusion and / or tableting.

[0056] The present invention has no special requirements for the preparation method of the catalyst. For the present invention, the preferred preparation method of the catalyst includes:

[0057] (a) obtaining zinc oxide nanorods for serving as an inert support;

[0058] (b) obtaining a precursor slurry containing catalyst active components;

[0059] (c) spraying the precursor slurry onto the zinc oxide nanorods by a spraying method, and calcining to obtain the catalyst.

[0060] The present invention has no special requirements on the types of raw materials for preparing the catalyst. The following is an exemplary description, but the scope of the present invention is not limited thereby.

[0061] For example, the active components of the catalyst include a main active component oxide and an auxiliary active component element oxide, wherein the main active component oxide includes vanadium oxide and titanium oxide; and the auxiliary active component element is selected from at least one of a sub-group metal element and a non-metal element.

[0062] For example, the vanadium source is one or more of metavanadate, vanadium oxide and orthovanadate.

[0063] For example, the titanium source is one or more of titanate, titanium oxide, and titanium halide.

[0064] For example, when the auxiliary active component element is preferably one or more of zirconium, niobium, tungsten, phosphorus and boron; the zirconium source is, for example, at least one of zirconium oxide and zirconium silicate.

[0065] For example, the niobium source is at least one of niobium oxalate and niobium pentachloride.

[0066] For example, the tungsten source is at least one of tungstic acid and ammonium metatungstate.

[0067] For example, the phosphorus source is at least one of phosphoric acid and diammonium phosphate.

[0068] For example, the boron source is at least one of boric acid and ammonium pentaborate.

[0069] In the present invention, there are no special requirements for spraying and roasting. For the present invention, the exemplary description is given, but the scope of the present invention is not limited thereto. In step (c), for example, the spraying temperature is 60-180°C, preferably 80-160°C, for example, 80°C, 100°C, 120°C, 140°C, 160°C.

[0070] For example, the calcination temperature is 350-500°C, preferably 400-480°C, for example 400°C, 450°C, 480°C.

[0071] For example, the calcination time is 2-10 hours, preferably, the calcination time is 3-6 hours.

[0072] The present invention provides a method for producing homoanhydride, which uses a fixed bed reactor, in the presence of the catalyst of the present invention, raw material durene and oxygen-containing gas contact, the contact conditions include: the mass concentration of durene is 10-40g / cm 3 , gas hourly volume space velocity is 4000-8000hr -1 , the reaction temperature is 350-500°C, and the reaction pressure is normal pressure.

[0073] According to a preferred embodiment of the present invention, the contact conditions include: the mass concentration of durene is 15-30 g / cm 3 , gas hourly volume space velocity is 4000-6000hr -1, the reaction temperature is 360-480°C, the reaction pressure is normal pressure, and the oxygen-containing gas is air.

[0074] In the present invention, in order to prepare a uniform slurry, the precursor slurry in step (b) can be continuously heated and stirred during preparation, which is a well-known technique in the art. According to a preferred embodiment of the present invention, the slurry temperature is preferably heated to 60-100° C., preferably, the slurry temperature is 70-90° C. This can improve the target yield of the catalyst.

[0075] According to a preferred embodiment of the present invention, the stirring time is 4-12 hours, preferably, the stirring time is 6-10 hours.

[0076] According to a preferred embodiment of the present invention, further, the particle size of the catalyst is 40-60 mesh.

[0077] The present invention will be described in detail below by way of examples. In the following examples, the homoanhydride is synthesized by the durene vapor phase oxidation method, and the mass yield of the homoanhydride is calculated as follows:

[0078]

[0079] The mass fraction of homogenized anhydride in the solid product was analyzed by Waters alliance series high performance liquid chromatography equipped with Waters e2695 separation module and PDA detector. The reagents used in the following examples are all analytically pure commercial products of Sinopharm Chemical Reagent Co., Ltd. The mechanical stability of the catalyst in the following examples is represented by the attrition rate, which is measured by KM-4D particle attrition tester of Dalian Penghui Technology Development Co., Ltd.

[0080] The following further describes the contents of the present invention in conjunction with examples, but does not serve as a limitation of the present invention. The protection scope of the present invention shall be based on the contents recorded in the claims, and any replacement of equivalent technical means made according to the specification shall not depart from the protection scope of the present invention.

[0081] In the embodiment of the present invention, the crystalline structure of zinc oxide is measured by a Rigaku D / max 2500v / pc X-ray diffractometer; the morphology of zinc oxide is measured by a Hitachi SU8000 electron microscope.

[0082] Preparation Example 1

[0083] Weigh 3g zinc acetate and 4g PEG 20000 and dissolve them in 10g deionized water. Stir until completely dissolved, then add 200g ethanol to obtain a mixed solution and stir for 2h. When white foam is observed in the solution, add 6g NaOH and continue stirring until completely dissolved, which takes about 8h. Pour the mixed solution into a high-temperature and high-pressure stainless steel hydrothermal reactor containing a polyethylene tetrafluoroethylene liner, place the reactor in a 120℃ constant temperature drying oven, and react for 12h. After the reaction is completed, take it out, cool it to room temperature, take out the liner, pour out the supernatant, and filter the remaining part and wash it three times with deionized water and ethanol respectively. The obtained powder is dried in a 60℃ constant temperature drying oven for 6h, then placed in a muffle furnace and calcined at 450℃ for 4h, and the catalyst inert carrier is obtained by tableting.

[0084] SEM( Figure 1 ) characterization found that its microstructure is in the shape of a wire rod, with a clear one-dimensional structure, a diameter of about 30-50nm, a length of about 3.5-3.9μm, and has good repeatability and uniformity. Figure 2 ) characterization found that it has obvious diffraction peaks at 2θ=31.9°, 34.5°, and 36.3°, and the characteristic peaks are consistent with the standard hexagonal wurtzite zinc oxide standard card (JCPDS, No.36-1451).

[0085] Preparation Example 2

[0086] Weigh 3g zinc acetate and 4g PEG 20000 and dissolve them in 50g deionized water. Stir until completely dissolved, then add 200g ethanol to obtain a mixed solution and stir for 2h. When white foam is observed in the solution, add 6g NaOH and continue stirring until completely dissolved, which takes about 8h. Pour the mixed solution into a high-temperature and high-pressure stainless steel hydrothermal reactor containing a polyethylene tetrafluoroethylene liner, place the reactor in a 120℃ constant temperature drying oven, and react for 12h. After the reaction is completed, take it out, cool it to room temperature, take out the liner, pour out the supernatant, and filter the remaining part and wash it three times with deionized water and ethanol respectively. The obtained powder is dried in a 60℃ constant temperature drying oven for 6h, then placed in a muffle furnace and roasted at 450℃ for 4h, and the catalyst inert carrier is obtained by tableting.

[0087] The SEM image and XRD are similar to those in the embodiment, with a diameter of about 40-60 nm and a length of about 3.2-3.7 μm.

[0088] Preparation Example 3

[0089] Weigh 3g zinc acetate and 4g PEG 20000 and dissolve them in 80g deionized water. Stir until completely dissolved, then add 200g ethanol to obtain a mixed solution and stir for 2h. When white foam is observed in the solution, add 6g NaOH and continue stirring until completely dissolved, which takes about 8h. Pour the mixed solution into a high-temperature and high-pressure stainless steel hydrothermal reactor containing a polyethylene tetrafluoroethylene liner, place the reactor in a 100℃ constant temperature drying oven, and react for 12h. After the reaction is completed, take it out, cool it to room temperature, take out the liner, pour out the supernatant, and filter the remaining part and wash it three times with deionized water and ethanol respectively. The obtained powder is dried in a 60℃ constant temperature drying oven for 6h, then placed in a muffle furnace and roasted at 450℃ for 4h, and the catalyst inert carrier is obtained by tableting.

[0090] The SEM image and XRD are similar to those in the embodiment, with a diameter of about 40-70 nm and a length of about 3.0-3.5 μm.

[0091] Preparation Example 4

[0092] Weigh 3g zinc acetate and 4g PEG 20000 and dissolve them in 200g deionized water. Stir until completely dissolved, then add 200g ethanol to obtain a mixed solution and stir for 2h. When white foam is observed in the solution, add 6g NaOH and continue stirring until completely dissolved, which takes about 8h. Pour the mixed solution into a high-temperature and high-pressure stainless steel hydrothermal reactor containing a polyethylene tetrafluoroethylene liner, place the reactor in a 100℃ constant temperature drying oven, and react for 12h. After the reaction is completed, take it out, cool it to room temperature, take out the liner, pour out the supernatant, and filter the remaining part and wash it three times with deionized water and ethanol respectively. The obtained powder is dried in a 60℃ constant temperature drying oven for 6h, then placed in a muffle furnace and roasted at 450℃ for 4h, and the catalyst inert carrier is obtained by tableting. Its diameter is about 80-120nm and its length is about 1.0-2.0μm.

[0093] Example 1

[0094] A spray-molded catalyst for producing homoanhydride was prepared. The carrier was the zinc oxide nanowire with a one-dimensional linear structure prepared in Preparation Example 1, the vanadium source was ammonium metavanadate, the titanium source was titanium dioxide, and the co-catalyst components were phosphorus and niobium:

[0095] Weigh 80g of oxalic acid and 300mL of distilled water in a three-necked flask, stir and heat to 80°C, and dissolve all the oxalic acid to obtain an oxalic acid solution. Slowly add 38g of ammonium metavanadate to the prepared oxalic acid solution, and continue to stir until the oxalic acid and ammonium metavanadate react completely to obtain a vanadium oxalate solution. Continue to add 1.2g of ammonium dihydrogen phosphate and 0.8g of niobium oxalate to the solution. Add 120g of titanium dioxide to the solution, control the solution temperature at 80°C and stir for 6h. Take a certain mass of the zinc oxide nanowire carrier prepared above and put it into a sprayer, spray at a temperature of 110°C, and evenly spray the above slurry onto the zinc oxide nanowire carrier. Based on the total weight of the catalyst, the spraying amount of the active component is 10wt%. The sprayed catalyst is placed in a muffle furnace, calcined at a temperature of 450°C, calcined for 3h, and cooled naturally to obtain the catalyst. Using durene and air as raw materials, a fixed bed reactor is used to prepare homoanhydride in the presence of a catalyst; the reaction process and temperature conditions are as follows: the mass concentration of durene is 20 g / cm 3 , gas hourly volume space velocity is 5000hr -1 The reaction temperature was 390°C and the reaction pressure was normal pressure. The yield of the anhydride was 83.1 wt%. 10 g of the catalyst was placed in a particle wear tester to measure the wear rate. The parameters of the instrument were: the inner diameter of the grinding cylinder The length of the grinding drum is 150 mm, the inner baffle of the grinding drum is 150 mm long and 18 mm high, the rotating speed of the grinding drum is 30 r / min, and the grinding time is 10 min. The catalyst attrition rate is measured to be 0.15%.

[0096] Example 2

[0097] A spray-molded catalyst for producing homoanhydride was prepared. The carrier was the zinc oxide nanowire with a one-dimensional linear structure prepared in Preparation Example 1, the vanadium source was ammonium metavanadate, the titanium source was titanium dioxide, and the co-catalyst components were boron and niobium:

[0098] Weigh 80g of oxalic acid and 300mL of distilled water in a three-necked flask, stir and heat to 80°C, and dissolve all the oxalic acid to obtain an oxalic acid solution. Slowly add 38g of ammonium metavanadate to the prepared oxalic acid solution, and continue to stir until the oxalic acid and ammonium metavanadate react completely to obtain a vanadium oxalate solution. Continue to add 0.5g of boric acid and 0.8g of niobium oxalate to the solution. Add 120g of titanium dioxide to the solution, control the solution temperature at 80°C and stir for 6h. Take a certain mass of the zinc oxide nanowire carrier prepared above and put it into a sprayer, spray at a temperature of 110°C, and evenly spray the above slurry onto the zinc oxide nanowire carrier. Based on the total weight of the catalyst, the spraying amount of the active component is 10wt%. The sprayed catalyst is placed in a muffle furnace, calcined at a temperature of 450°C, calcined for 3h, and cooled naturally to obtain the catalyst. Using durene and air as raw materials, a fixed bed reactor is used to prepare homoanhydride in the presence of a catalyst; the reaction process and temperature conditions are as follows: the mass concentration of durene is 20 g / cm 3 , gas hourly volume space velocity is 5000hr -1 The reaction temperature was 390°C and the reaction pressure was normal pressure. The yield of the anhydride was 83.6 wt%. 10 g of the catalyst was placed in a particle wear tester to measure the wear rate. The parameters of the instrument were: the inner diameter of the grinding cylinder The length of the grinding drum is 150 mm, the inner baffle of the grinding drum is 150 mm long and 18 mm high, the rotating speed of the grinding drum is 30 r / min, and the grinding time is 10 min. The catalyst attrition rate is measured to be 0.14%.

[0099] Example 3

[0100] A spray-molded catalyst for producing homoanhydride was prepared. The carrier was the zinc oxide nanowire with a one-dimensional linear structure prepared in Preparation Example 1, the vanadium source was ammonium metavanadate, the titanium source was titanium dioxide, and the co-catalyst components were phosphorus and tungsten:

[0101] Weigh 80g of oxalic acid and 300mL of distilled water in a three-necked flask, stir and heat to 80°C, and dissolve all the oxalic acid to obtain an oxalic acid solution. Slowly add 38g of ammonium metavanadate to the prepared oxalic acid solution, and continue to stir until the oxalic acid and ammonium metavanadate react completely to obtain a vanadium oxalate solution. Continue to add 1.2g of ammonium dihydrogen phosphate and 1g of ammonium metatungstate to the solution. Add 120g of titanium dioxide to the solution, control the solution temperature at 80°C and stir for 6h. Take a certain mass of the zinc oxide nanowire carrier prepared above and put it into a sprayer, spray at a temperature of 110°C, and evenly spray the above slurry onto the zinc oxide nanowire carrier. Based on the total weight of the catalyst, the spraying amount of the active component is 10wt%. The sprayed catalyst is placed in a muffle furnace, calcined at a temperature of 450°C, calcined for 3h, and cooled naturally to obtain the catalyst. Using durene and air as raw materials, a fixed bed reactor is used to prepare homoanhydride in the presence of a catalyst; the reaction process and temperature conditions are as follows: the mass concentration of durene is 20 g / cm 3 , gas hourly volume space velocity is 5000hr -1 The reaction temperature was 390°C and the reaction pressure was normal pressure. The yield of the anhydride was 84.4 wt%. 10 g of the catalyst was placed in a particle wear tester to measure the wear rate. The parameters of the instrument were: the inner diameter of the grinding cylinder The length of the grinding drum is 150 mm, the inner baffle of the grinding drum is 150 mm long and 18 mm high, the rotating speed of the grinding drum is 30 r / min, and the grinding time is 10 min. The catalyst attrition rate is measured to be 0.16%.

[0102] Example 4

[0103] A spray-molded catalyst for producing homoanhydride was prepared. The carrier was the zinc oxide nanowire with a one-dimensional linear structure prepared in Preparation Example 1, the vanadium source was ammonium metavanadate, the titanium source was titanium dioxide, and the co-catalyst components were boron and tungsten:

[0104] Weigh 80g of oxalic acid and 300mL of distilled water in a three-necked flask, stir and heat to 80°C, and dissolve all the oxalic acid to obtain an oxalic acid solution. Slowly add 38g of ammonium metavanadate to the prepared oxalic acid solution, and continue to stir until the oxalic acid and ammonium metavanadate react completely to obtain a vanadium oxalate solution. Continue to add 0.5g of boric acid and 1g of ammonium metatungstate to the solution. Add 120g of titanium dioxide to the solution, control the solution temperature at 80°C and stir for 6h. Take a certain mass of the zinc oxide nanowire carrier prepared above and put it into a sprayer, spray at a temperature of 110°C, and evenly spray the above slurry onto the zinc oxide nanowire carrier. Based on the total weight of the catalyst, the spraying amount of the active component is 10wt%. The sprayed catalyst is placed in a muffle furnace, calcined at a temperature of 450°C, calcined for 3h, and cooled naturally to obtain the catalyst. Using durene and air as raw materials, a fixed bed reactor is used to prepare homoanhydride in the presence of a catalyst; the reaction process and temperature conditions are as follows: the mass concentration of durene is 20 g / cm 3 , gas hourly volume space velocity is 5000hr -1 The reaction temperature was 390°C and the reaction pressure was normal pressure. The yield of the anhydride was 83.3 wt%. 10 g of the catalyst was placed in a particle wear tester to measure the wear rate. The parameters of the instrument were: the inner diameter of the grinding cylinder The length of the grinding drum is 150 mm, the inner baffle of the grinding drum is 150 mm long and 18 mm high, the rotating speed of the grinding drum is 30 r / min, and the grinding time is 10 min. The catalyst attrition rate is measured to be 0.13%.

[0105] Example 5

[0106] A spray-molded catalyst for producing homoanhydride was prepared. The carrier was the zinc oxide nanowire with a one-dimensional linear structure prepared in Preparation Example 1, the vanadium source was ammonium metavanadate, the titanium source was titanium dioxide, and the co-catalyst components were phosphorus, niobium and tungsten:

[0107] Weigh 80g of oxalic acid and 300mL of distilled water in a three-necked flask, stir and heat to 80°C, and dissolve all the oxalic acid to obtain an oxalic acid solution. Slowly add 38g of ammonium metavanadate to the prepared oxalic acid solution, and continue to stir until the oxalic acid and ammonium metavanadate react completely to obtain a vanadium oxalate solution. Continue to add 1.2g of ammonium dihydrogen phosphate, 0.4g of niobium oxalate and 0.6g of ammonium metatungstate to the solution. Add 120g of titanium dioxide to the solution, control the solution temperature at 80°C and stir for 6h. Take a certain mass of the zinc oxide nanowire carrier prepared above and put it into a sprayer, spray at a temperature of 110°C, and evenly spray the above slurry onto the zinc oxide nanowire carrier. Based on the total weight of the catalyst, the spraying amount of the active component is 10wt%. The sprayed catalyst is placed in a muffle furnace, calcined at a temperature of 450°C, calcined for 3h, and cooled naturally to obtain the catalyst. Using durene and air as raw materials, a fixed bed reactor is used to prepare homoanhydride in the presence of a catalyst; the reaction process and temperature conditions are as follows: the mass concentration of durene is 20 g / cm 3 , gas hourly volume space velocity is 5000hr -1 The reaction temperature was 390°C and the reaction pressure was normal pressure. The yield of the anhydride was 85.1 wt%. 10 g of the catalyst was placed in a particle attrition instrument to measure the attrition rate. The parameters of the instrument were: the inner diameter of the grinding cylinder The length of the grinding drum is 150 mm, the inner baffle of the grinding drum is 150 mm long and 18 mm high, the rotating speed of the grinding drum is 30 r / min, and the grinding time is 10 min. The catalyst attrition rate is measured to be 0.15%.

[0108] It can be seen from Examples 1-5 that the catalyst has a better product yield when the zinc oxide nanowires with a one-dimensional linear structure are used as a carrier and the auxiliary active components are selected from phosphorus, niobium and tungsten.

[0109] Example 6

[0110] A spray-molded catalyst for producing homogenized anhydride was prepared. The carrier was the zinc oxide nanowire prepared in Preparation Example 2, the vanadium source was ammonium metavanadate, the titanium source was titanium dioxide, and the co-catalyst components were phosphorus, niobium and tungsten:

[0111] Weigh 80g of oxalic acid and 300mL of distilled water in a three-necked flask, stir and heat to 80°C, and completely dissolve the oxalic acid to obtain an oxalic acid solution. Slowly add 38g of ammonium metavanadate to the prepared oxalic acid solution, and continue to stir until the oxalic acid and ammonium metavanadate react completely to obtain a vanadium oxalate solution. Continue to add 1.2g of ammonium dihydrogen phosphate, 0.4g of niobium oxalate and 0.6g of ammonium metatungstate to the solution. Add 120g of titanium dioxide to the solution, control the solution temperature at 80°C and stir for 6h. Take a certain mass of the zinc oxide nanowire carrier obtained in the above preparation example 2 and put it into the sprayer, the spraying temperature is 110°C, and the above slurry is evenly sprayed on the zinc oxide nanowire carrier. Based on the total weight of the catalyst, the spraying amount of the active component is 10wt%. The sprayed catalyst is placed in a muffle furnace, the roasting temperature is 450°C, the roasting time is 3h, and the catalyst is obtained after natural cooling. Using durene and air as raw materials, a fixed bed reactor is used to prepare homoanhydride in the presence of a catalyst; the reaction process and temperature conditions are as follows: the mass concentration of durene is 20 g / cm 3 , gas hourly volume space velocity is 5000hr -1 The reaction temperature was 390°C and the reaction pressure was normal pressure. The yield of the anhydride was 85.4 wt%. 10 g of the catalyst was placed in a particle wear tester to measure the wear rate. The parameters of the instrument were: the inner diameter of the grinding cylinder The length of the grinding drum is 150 mm, the inner baffle of the grinding drum is 150 mm long and 18 mm high, the rotating speed of the grinding drum is 30 r / min, and the grinding time is 10 min. The catalyst attrition rate is measured to be 0.18%.

[0112] Example 7

[0113] A spray-molded catalyst for producing homoanhydride was prepared, wherein the carrier was the zinc oxide nanowire prepared in Preparation Example 3, the vanadium source was ammonium metavanadate, the titanium source was titanium dioxide, and the co-catalyst components were phosphorus, niobium and tungsten:

[0114] Weigh 80g of oxalic acid and 300mL of distilled water in a three-necked flask, stir and heat to 80°C, and completely dissolve the oxalic acid to obtain an oxalic acid solution. Slowly add 38g of ammonium metavanadate to the prepared oxalic acid solution, and continue to stir until the oxalic acid and ammonium metavanadate react completely to obtain a vanadium oxalate solution. Continue to add 1.2g of ammonium dihydrogen phosphate, 0.4g of niobium oxalate and 0.6g of ammonium metatungstate to the solution. Add 120g of titanium dioxide to the solution, control the solution temperature at 80°C and stir for 6h. Take a certain mass of the zinc oxide nanowire carrier obtained in the above preparation example 3 and put it into the sprayer, the spraying temperature is 110°C, and the above slurry is evenly sprayed on the zinc oxide nanowire carrier. Based on the total weight of the catalyst, the spraying amount of the active component is 10wt%. The sprayed catalyst is placed in a muffle furnace, the roasting temperature is 450°C, the roasting time is 3h, and the catalyst is obtained after natural cooling. Using durene and air as raw materials, a fixed bed reactor is used to prepare homoanhydride in the presence of a catalyst; the reaction process and temperature conditions are as follows: the mass concentration of durene is 20 g / cm 3 , gas hourly volume space velocity is 5000hr -1 The reaction temperature was 390°C and the reaction pressure was normal pressure. The yield of the anhydride was 84.9 wt%. 10 g of the catalyst was placed in a particle attrition instrument to measure the attrition rate. The parameters of the instrument were: the inner diameter of the grinding cylinder The length of the grinding drum is 150 mm, the inner baffle of the grinding drum is 150 mm long and 18 mm high, the rotating speed of the grinding drum is 30 r / min, and the grinding time is 10 min. The catalyst attrition rate is measured to be 0.19%.

[0115] It can be seen from Examples 6 and 7 that, within the scope of the present invention, by changing the preparation conditions, the prepared zinc oxide nanowires are still an excellent inert carrier for the catalyst for the gas-phase oxidation of durene to prepare homoanhydride.

[0116] Example 8

[0117] A spray-molded catalyst for producing homoanhydride was prepared, wherein the carrier was the zinc oxide nanowire prepared in Preparation Example 4, the vanadium source was ammonium metavanadate, the titanium source was titanium dioxide, and the co-catalyst components were phosphorus, niobium and tungsten:

[0118] Weigh 80g of oxalic acid and 300mL of distilled water in a three-necked flask, stir and heat to 80°C, and completely dissolve the oxalic acid to obtain an oxalic acid solution. Slowly add 38g of ammonium metavanadate to the prepared oxalic acid solution, and continue to stir until the oxalic acid and ammonium metavanadate react completely to obtain a vanadium oxalate solution. Continue to add 1.2g of ammonium dihydrogen phosphate, 0.4g of niobium oxalate and 0.6g of ammonium metatungstate to the solution. Add 120g of titanium dioxide to the solution, control the solution temperature at 80°C and stir for 6h. Take a certain mass of the zinc oxide nanowire carrier obtained in the above preparation example 3 and put it into the sprayer, the spraying temperature is 110°C, and the above slurry is evenly sprayed on the zinc oxide nanowire carrier. Based on the total weight of the catalyst, the spraying amount of the active component is 10wt%. The sprayed catalyst is placed in a muffle furnace, the roasting temperature is 450°C, the roasting time is 3h, and the catalyst is obtained after natural cooling. Using durene and air as raw materials, a fixed bed reactor is used to prepare homoanhydride in the presence of a catalyst; the reaction process and temperature conditions are as follows: the mass concentration of durene is 20 g / cm 3 , gas hourly volume space velocity is 5000hr -1 The reaction temperature was 390°C and the reaction pressure was normal pressure. The yield of the anhydride was 82.2 wt%. 10 g of the catalyst was placed in a particle wear tester to measure the wear rate. The parameters of the instrument were: the inner diameter of the grinding cylinder The length of the grinding drum is 150 mm, the inner baffle of the grinding drum is 150 mm long and 18 mm high, the rotating speed of the grinding drum is 30 r / min, and the grinding time is 10 min. The catalyst attrition rate is measured to be 0.32%.

[0119] It can be seen from Example 8 that changing the mass ratio of water and ethanol during the preparation of zinc oxide nanowires will affect their carrier effect. Excessively increasing the mass ratio of water and ethanol during the preparation process will lead to poor carrier performance of zinc oxide nanowires, and zinc oxide nanowires with a one-dimensional linear structure with a high aspect ratio have excellent carrier performance.

[0120] Comparative Example 1

[0121] A spray-molded catalyst for producing homogenized anhydride was prepared. The carrier was nano zinc oxide (article number: Z820772) produced by MacLean Company, the vanadium source was ammonium metavanadate, the titanium source was titanium dioxide, and the co-catalyst components were phosphorus, niobium and tungsten:

[0122] Weigh 80g of oxalic acid and 300mL of distilled water in a three-necked flask, stir and heat to 80°C, and dissolve all the oxalic acid to obtain an oxalic acid solution. Slowly add 38g of ammonium metavanadate to the prepared oxalic acid solution, and continue to stir until oxalic acid and ammonium metavanadate react completely to obtain a vanadium oxalate solution. Continue to add 1.2g of ammonium dihydrogen phosphate, 0.4g of niobium oxalate and 0.6g of ammonium metatungstate to the solution. Add 120g of titanium dioxide to the solution, control the solution temperature at 80°C and stir for 6h. Take a certain mass of the above-mentioned pressed-sheet-formed nano zinc oxide carrier and put it into a sprayer, spray at a temperature of 110°C, and evenly spray the above slurry onto the zinc oxide nanowire carrier. Based on the total weight of the catalyst, the spraying amount of the active component is 10wt%. The sprayed catalyst is placed in a muffle furnace, calcined at 450°C, calcined for 3h, and cooled naturally to obtain the catalyst. Using durene and air as raw materials, a fixed bed reactor is used to prepare homoanhydride in the presence of a catalyst; the reaction process and temperature conditions are as follows: the mass concentration of durene is 20 g / cm 3 , gas hourly volume space velocity is 5000hr -1 The reaction temperature was 390°C and the reaction pressure was normal pressure. The yield of the anhydride was 76.3 wt%. 10 g of the catalyst was placed in a particle wear tester to measure the wear rate. The parameters of the instrument were: the inner diameter of the grinding cylinder The length of the grinding drum is 150 mm, the inner baffle of the grinding drum is 150 mm long and 18 mm high, the rotating speed of the grinding drum is 30 r / min, and the grinding time is 10 min. The catalyst attrition rate is measured to be 0.44%.

[0123] Comparative Example 2

[0124] A spray-molded catalyst for producing homoanhydride is prepared, wherein the carrier is an industrial-grade ceramic ring, the vanadium source is ammonium metavanadate, the titanium source is titanium dioxide, and the co-catalyst components are phosphorus, niobium and tungsten:

[0125] Weigh 80g of oxalic acid and 300mL of distilled water in a three-necked flask, stir and heat to 80°C, and dissolve all the oxalic acid to obtain an oxalic acid solution. Slowly add 38g of ammonium metavanadate to the prepared oxalic acid solution, and continue to stir until the oxalic acid and ammonium metavanadate react completely to obtain a vanadium oxalate solution. Continue to add 1.2g of ammonium dihydrogen phosphate, 0.4g of niobium oxalate and 0.6g of ammonium metatungstate to the solution. Add 120g of titanium dioxide to the solution, control the solution temperature at 80°C and stir for 6h. Take a certain mass of the above-mentioned porcelain ring carrier and put it into the sprayer, spray at 110°C, and evenly spray the above slurry onto the zinc oxide nanowire carrier. Based on the total weight of the catalyst, the spraying amount of the active component is 10wt%. The sprayed catalyst is placed in a muffle furnace, calcined at 450°C, calcined for 3h, and cooled naturally to obtain the catalyst. Using durene and air as raw materials, a fixed bed reactor is used to prepare homoanhydride in the presence of a catalyst; the reaction process and temperature conditions are as follows: the mass concentration of durene is 20 g / cm 3 , gas hourly volume space velocity is 5000hr -1 The reaction temperature was 390°C and the reaction pressure was normal pressure. The yield of the anhydride was 80.1 wt%. 10 g of the catalyst was placed in a particle wear tester to measure the wear rate. The parameters of the instrument were: the inner diameter of the grinding cylinder The length of the grinding drum is 150 mm, the inner baffle of the grinding drum is 150 mm long and 18 mm high, the rotating speed of the grinding drum is 30 r / min, and the grinding time is 10 min. The catalyst attrition rate is measured to be 0.63%.

[0126] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

[0127] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A catalyst for preparing homoanhydride by gas phase oxidation of durene, characterized in that: The catalyst comprises an inert carrier and an active component; the inert carrier is a zinc oxide nanorod.

2. The catalyst according to claim 1, wherein The zinc oxide nanorods have obvious diffraction peaks at 2θ of 31.9°, 34.5° and 36.3°; and / or The aspect ratio of the zinc oxide nanorods is 40-130, preferably 42-55; and / or The length of the zinc oxide nanorods is 3.0-3.9 μm; and / or The diameter of the zinc oxide nanorods is 30-70 nm; and / or The crystalline phase of zinc oxide nanorods is hexagonal zincite.

3. The catalyst according to claim 1 or 2, wherein Based on the total weight of the catalyst, the content of the carrier is 60-97wt%; Based on the total weight of the catalyst, the active component is calculated based on the weight of its corresponding oxide, and the content of the active component is 1-50wt%, preferably, the content of the active component is 3-40wt%; and / or The active components of the catalyst include a main active component oxide and an auxiliary active component element oxide, wherein the main active component oxide includes vanadium oxide and titanium oxide; The auxiliary active component element is selected from at least one of the sub-group metal elements and non-metal elements; Preferably, the mass ratio of the vanadium oxide, titanium oxide, and oxide of the auxiliary active component element is (0.005-0.5):1:(0.003-0.28); Preferably, The subgroup metal element includes one or more of zirconium, niobium and tungsten; and / or The non-metallic element includes one or more of phosphorus and boron.

4. The catalyst according to claim 3, wherein The mass ratio of the vanadium oxide, titanium oxide, subgroup metal element oxide and non-metal element oxide is (0.005-0.5):1:(0.0001-0.2):(0.001-0.08); Preferably, the mass ratio of vanadium oxide, titanium oxide, subgroup metal element oxide and non-metal element oxide is (0.05-0.45):1:(0.0005-0.002):(0.002-0.05); Preferably, the auxiliary active components include niobium oxide, tungsten oxide and phosphorus oxide; preferably, the mass ratio of the three is 0.01-1:0.01-1:

1.

5. The catalyst according to any one of claims 1 to 4, wherein The preparation method of the inert carrier comprises the following steps: (1) obtaining a mixed solution including a zinc source, polyethylene glycol, water, ethanol and sodium hydroxide; (2) transferring the mixed solution to a hydrothermal reactor for hydrothermal reaction; (3) washing, filtering, drying, calcining and optionally forming the reaction product after the hydrothermal reaction is completed; Wherein, in step (1), the mass ratio of water to ethanol is 0-2:1, preferably 0.005-0.5:1; Preferably, in step (1), the polyethylene glycol is one or more of polyethylene glycol 2000, polyethylene glycol 10000 and polyethylene glycol 20000, preferably polyethylene glycol 20000.

6. The catalyst according to claim 5, wherein In step (1), the zinc source is one or more of zinc acetate, zinc sulfate and zinc nitrate, preferably zinc acetate; and / or The weight ratio of zinc source, polyethylene glycol, water, ethanol and sodium hydroxide is 0.001-0.1: 0.001-0.1: 0.005-0.5: 1: 0.01-0.1; and / or In step (2), the conditions of the hydrothermal reaction include: a reaction temperature of 80-200° C., preferably 100-150° C.; and / or a reaction time of 8-24 h, preferably 10-18 h; In step (3), the detergent is one or more of water, methanol and ethanol, preferably, the detergent is water and / or ethanol; The drying temperature is 40-100°C, preferably 60-80°C; and / or The calcination temperature is 300-600°C, preferably 400-500°C; and / or The forming method is extrusion and / or tableting.

7. The method for preparing the catalyst according to any one of claims 1 to 6, characterized in that: The method includes: (a) obtaining zinc oxide nanorods for serving as an inert support; (b) obtaining a precursor slurry containing catalyst active components; (c) spraying the precursor slurry onto the zinc oxide nanorods by a spraying method, and calcining to obtain the catalyst.

8. The preparation method according to claim 7, wherein: The active components of the catalyst include a main active component oxide and an auxiliary active component element oxide, wherein the main active component oxide includes vanadium oxide and titanium oxide; the auxiliary active component element is selected from at least one of a sub-group metal element and a non-metal element; The vanadium source is one or more of metavanadate, vanadium oxide and orthovanadate; and / or The titanium source is one or more of titanate, titanium oxide and titanium halide; and / or When the auxiliary active component element is preferably one or more of zirconium, niobium, tungsten, phosphorus and boron; The zirconium source is at least one of zirconium oxide and zirconium silicate; The niobium source is at least one of niobium oxalate and niobium pentachloride; The tungsten source is at least one of tungstic acid and ammonium metatungstate; The phosphorus source is at least one of phosphoric acid and diammonium phosphate; The boron source is at least one of boric acid and ammonium pentaborate.

9. The preparation method according to claim 7 or 8, wherein: In step (c), Spraying temperature 60-180°C, preferably 80-160°C; and / or The calcination temperature is 350-500°C, preferably 400-480°C.

10. A method for producing a homogenized anhydride, characterized in that: A fixed bed reactor is used, in the presence of the catalyst according to any one of claims 1 to 5, the raw material durenyl is contacted with an oxygen-containing gas, wherein the contact conditions include: the mass concentration of durenyl is 10-40 g / cm 3 , gas hourly volume space velocity is 4000-8000hr -1 , the reaction temperature is 350-500°C, and the reaction pressure is normal pressure; preferably, The contact conditions include: the mass concentration of durene is 15-30 g / cm 3 , gas hourly volume space velocity is 4000-6000hr -1 , the reaction temperature is 360-480°C, the reaction pressure is normal pressure, and the oxygen-containing gas is air.

Citation Information

Patent Citations

  • Photocatalytic material with visible light response capability and core-shell structure, and preparation method

    CN103801285A

  • Catalyst for preparation of pyromellitic dianhydride from durene

    CN107866257A

  • Multi-sandwich composite catalyst and preparation method and application thereof

    CN110038590A

  • Pyromellitic dianhydride catalyst and preparation method thereof

    CN112657484A

  • C / ZnO / BiOI ternary composite photocatalytic material

    CN112844425A